Constitute-Based Religious Moderation Education - Jumhur, Jumhur; Wasilah, Wasilah (Al-Hayat: Journal of Islamic Education, 2023)
This paper specifically discusses the integration of the Islamic boarding school education system with the teachings of the Qadariyah wa Naqsabandiyah order practised by the Palembang Aulia Cendekia Islamic boarding school and its impact on religious moderation education for the Palembang Muslim community. This research was conducted at the Qadariyah wa Naqsabandiyah congregation in Palembang, located at the Aulia Cendikia Islamic Boarding School. Data collection techniques using observation and interviews. This research found that by carrying out the teachings of the Qadariyah wa Naqsabandiyah order, a person will gain a deep love for God; the reflection of love for God is to love all of His creation so that with that love gives birth to an attitude of tolerance, compassion, and ends in an attitude of mutual respect between humans. In addition, it was also found that by practising the teachings of the Qadariyah wa Naqsabandiyah order, at the same time, one has implemented the three pillars of religious moderation; moderation of thought, movement, and deed. The dynamic dialogue between text and context implements thought moderation. Movement moderation is reflected in Islamic da'wah, or disseminating Islamic teachings with courtesy, compassion, and gentleness. Meanwhile, the moderation of actions is manifested by integrating the tarekat values ??with education.